The diagnosis of inflammatory bowel disease is often unsupported in clinical practice. Issue 1 (January 2015) - Canavese, Gabriella; Villanacci, Vincenzo; Sapino, Anna; Rocca, Rodolfo; Daperno, Marco; Suriani, Renzo; Maletta, Francesca; Cassoni, Paola; ,
Abstract: Background: The diagnosis of inflammatory bowel disease can be challenging and requires the efforts of a multidisciplinary team. We performed a retrospective analysis with the aim of evaluating the adequacy of the prerequisites for arriving at an accurate histological diagnosis. Methods: The following parameters were considered as prerequisites for a diagnosis of inflammatory bowel disease: clinical and endoscopic data; proper sampling and handling of biopsies; and elementary microscopic lesions. We collected 345 cases from 13 centres. Results: The date of onset and treatment were available for 13% and 16% of the cases, respectively. Endoscopy information was accessible for 77% of the cases. Endoscopic mapping was completed in 13% of the cases. In no cases were the biopsies oriented on acetate strips. The diagnosis was conclusive in 47% of the cases. Activity, epithelial disruption and crypt distortion were described in 35% of the reports with a conclusive diagnosis. Conclusion: Our study showed that the diagnostic prerequisites were widely unfulfilled, although approximately half of the diagnoses were conclusive for inflammatory bowel disease. Thus, in our assessment of clinical practice: (1) clinicians seldom provide suitable clinical and/or endoscopic information for a histological diagnosis and (2) histopathological diagnoses of inflammatory bowel disease are often not supported by morphology.